2017
DOI: 10.1111/nph.14882
|View full text |Cite
|
Sign up to set email alerts
|

A retrotransposon in an HKT1 family sodium transporter causes variation of leaf Na+ exclusion and salt tolerance in maize

Abstract: Soil salinity is one of several major abiotic stresses that constrain maize productivity worldwide. An improved understanding of salt-tolerance mechanisms will thus enhance the breeding of salt-tolerant maize and boost productivity. Previous studies have indicated that the maintenance of leaf Na concentration is essential for maize salt tolerance, and the difference in leaf Na exclusion has previously been associated with variation in salt tolerance between maize varieties. Here, we report the identification a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
168
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 246 publications
(190 citation statements)
references
References 69 publications
6
168
1
Order By: Relevance
“…Common SNPs between the 50k and 9K iSelect platforms 22 aligned this association with a region recently shown to contain HvHKT1;5 20, 23 , and in the barley genome sequence HORVU4Hr1G087960, 140kb from the top scoring SNP (chr4H_638774955), was annotated as a homolog of OsHKT1;5. Considering this and previous functional studies 2427 we conclude that HORVU4Hr1G087960 is the Na + specific transporter HvHKT1;5 .…”
Section: Resultssupporting
confidence: 75%
“…Common SNPs between the 50k and 9K iSelect platforms 22 aligned this association with a region recently shown to contain HvHKT1;5 20, 23 , and in the barley genome sequence HORVU4Hr1G087960, 140kb from the top scoring SNP (chr4H_638774955), was annotated as a homolog of OsHKT1;5. Considering this and previous functional studies 2427 we conclude that HORVU4Hr1G087960 is the Na + specific transporter HvHKT1;5 .…”
Section: Resultssupporting
confidence: 75%
“…In this study,expression of HKT1:1 followed similar trend in both leaves and roots of salt stressed plants. Previous studies suggested that HKT family transporter proteins can mediate exclusion of Na + from leaves and roots by translocating shoot-to-rootand root-to-shoot Na + delivery by withdrwaing Na + from xylem stream into phloem (Munns et al, 2012; Hill et al, 2013; An et al, 2017; Zhang et al, 2018). Induction of HKT1:1 expression upon initial imposition of salt stress in both leaves and roots may promote Na + exclusion tolimit Na + toxcity in the respective tissues(Zhang et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies suggested that HKT family transporter proteins can mediate exclusion of Na + from leaves and roots by translocating shoot-to-rootand root-to-shoot Na + delivery by withdrwaing Na + from xylem stream into phloem (Munns et al, 2012; Hill et al, 2013; An et al, 2017; Zhang et al, 2018). Induction of HKT1:1 expression upon initial imposition of salt stress in both leaves and roots may promote Na + exclusion tolimit Na + toxcity in the respective tissues(Zhang et al, 2018). However, with increasing salt stress treatment time, the marginal expression of HKT1:1genemay regulate the retrevial of Na + from the xylem (Davenport et al, 2007; Ali et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that the long-distance transport of Na + from root to leave may continue to be active under high salt stress in Spartina . One of the explanations is that leaves of Spartina have salt glands (Nestler, 1977; Subudhi & Baisakh, 2011) and can secrete salt, so that high expression of SaHKT1 may not be required to shut down Na + transport compared to other plants (Jaime-Perez et al, 2017; M. Zhang et al, 2018).…”
Section: Discussionmentioning
confidence: 99%